TINJAUAN YURIDIS PEMBELIAN BARANG MELALUI TOKO ONLINE DENGAN E - COMMERCE YANG TIDAK SESUAI DENGAN PESANAN - MHD YUDA MULYAWAN SIMATUPANG; MEISSY .; PINONDANG .; ESTER PASARIBU; PERI GUSTIRANDA (LP2MTBM MAKARIOZ, 2020)
Formulated legal issues regarding the factors that lead to the purchase of goods through an online store with e-commerceand not on-demand and how the police role in the criminal act of buying and selling online. The method used is normativejuridical, which is reviewing regulations of the ITE LAW and the criminal CODE. Article 28 paragraph (1) of the ITE LAW onthe arrangement concerning the dissemination of a lying and misleading news that harms consumers. At the same time inarticle 45 paragraph (1) ITE LAW number 11 year 2008 about fraud or ITE crimes. The role of police in criminal investigationof online buying and selling fraud is done similarly to other conventional criminal acts where the investigation refers to thecriminal CODE.